Scoring systems for Oral Lichen Planus used by differently experienced raters - Gobbo, Margherita (Med Oral Patol Oral Cir Bucal, 2017)
BACKGROUND: Scoring systems have been widely used to evaluate the severity and activity of oral lichen planus (OLP). The aim of the present study was to compare two existing (one modified) scoring systems in the evaluation of OLP severity and correlation with pain. Three differently experienced raters were involved. MATERIAL AND METHODS: Consecutive patients with OLP were assessed for pain using the Visual Analogue Scale and examined at 10 intraoral sites before starting (T0) and three weeks after (T1) steroid therapy (Clobetasol). Three differently experienced raters evaluated photographs using two scoring systems designated White-Erosive-Atrophic (WEA) modified from an older WEA system (WEA-MOD) and Reticular-erythematous-Ulcerative (REU) systems. WEA-MOD Kendall’s W and interclass correlation coefficient were calculated and correlation between REU/WEA-MOD and pain was calculated using Spearman coefficient. RESULTS: Most patients showed lesions on buccal mucosa (85-93,5%) and maxillary/mandibular gingivae (31,8-31,2%), predominantly reticular. At T0, Kendall-W coefficients of 0.89 and 0.74 were obtained for the REU and WEA respectively. At T1, Kendall-W coefficients of 0.83 and 0.58 were obtained for the REU and WEA respectively. Interclass correlation coefficient ranged from 0.87 to 0.90 for REU and from 0.58 to 0.87 for WEA. REU and WEA scores significantly decreased after therapy (p<0.000) as well as VAS (p<0.05). REU score showed correlation with VAS. CONCLUSIONS: All the raters achieved comparable measures using REU whereas WEA and WEA-MOD seem less reproducible. REU seems to correlate to disease activity and pain. Key words:Oral lichen planus, scoring system, VAS, REU, WEA, rater.